Distinct adaptive mechanisms drive recovery from aneuploidy caused by loss of the Ulp2 SUMO protease - Hong-Yeoul Ryu (Nature Portfolio, 2018)
Transient aneuploidy enables cells to survive sudden environmental changes before longterm cellular adaptations are established. Here, the authors show that yeast cells respond to the acute loss of Ulp2 SUMO protease by rapid induction of aneuploidy, and reveal predictable long-term adaptation mechanisms that restore euploidy.